A review and assessment of effect of cutting fluids. (2021) - Ravi, S.; Gurusamy, P.; Mohanavel, V.
Abstract: Metal cutting generates heat due to resistance between the chip interface of the tool and the workpiece of the tool. The heat generated in the machining process will raise the temperature to a point where tool damage occurs resulting in higher cutting forces, increased surface roughness, reduced tool life and inaccuracies in machined part dimension. Different strategies are explained to safeguard to cutting from the produced heat energy throughout metal removing operations. The option of coated especially cutting tools is fashionable different and usually, it's an acceptable approach for machining onerous materials. It is an alternate way to use these lubricants in metal removing operation. Cutting fluids were implied to provide cooling effects as well as lubrication in between the workpiece of the tool and chip of the tool interfaces throughout the metal removing processes. As a result, necessary advantages will be easily reached in terms of providing high tool life, increased metal removing quality, and improved flow of the chip during metal removing operations. Given choice, a technique of application, depository, and destruction of these cutting fluids ought to be done rigorously administrated to get optimum lead to machining processes. Metal cutting fluids are applied to the efficiency of metal removing processes due to their cooling effects, flushing of a chip, and lubrication. Besides, they're a major supply of pollution from machining industries. Minimum Quantity of Lubrication (MQL), Mist lubrication, Maximum pressure lubrication. Cryogenic Machining is the alternative technique for desirable control of cutting temperature.